Tea Leaves - Francis H. Leggett & Co. (Salt Lake City, UT : Project Gutenberg, 2002)
"Tea Leaves" by Francis Leggett & Co. is a historical account likely written during the late 19th century. The book delves into various facets of tea, its cultivation, and its significant cultural impact, particularly in the wake of European demand and colonization efforts. It serves as a commentary on the social and economic aspects of tea consumption, along with the evolution of tea production in regions beyond China, such as India and Ceylon. At the start of "Tea Leaves," the authors introduce the significance of tea as a refreshing beverage and detail the historical misconceptions surrounding its origins, highlighting the changes in tea production and trade over the last century. They discuss the shift from tea solely imported from China to the emergence of English-produced teas in various global markets. This opening section emphasizes the beverage's cultural importance and the myriad of substitutes used before the wide acceptance of Chinese tea, leading into a broader examination of tea's journey through history and its integration into daily customs. (This is an automatically generated summary.)
Release date is 2002-10-01
This etext was produced by Richard and Margie Druery
Keywords: Tea; Tea -- History; Tea trade -- History; Tea -- Social aspects